Application of stem cells in the treatment of reproductive disorders in men and women: review article - Nazanin Rezaei; Saba Farzi; Hamid Taghinejad; Mahnaz Shafieian; Safoura Taheri (Mashhad University of Medical Sciences, 2017)
Introduction: Stem cells refer to those body's cells which are still undifferentiated and have proliferative power and the ability to differentiate into other types of cells in the body. Considering the importance and sensitivity of fertility in human societies and efforts to search for a solution to reduce fertility disorders in men and women, this review study was performed with aim to evaluate the application of stem cells in the treatment of reproductive disorders in women and men. Methods: In this review study, the information on the use of stem cells in the treatment of reproductive disorders in men and women was searched in databases such as SID, Magiran, PubMed, Irandoc, Iranmedx Scopus, Google scholar, web of science using the keywords of stem cells, infertility, reproductive disorders, men and women without time limitation. Data analysis was carried out qualitatively. Finally, 48 papers in English and Persian were used for the regulation of the article. Results: The ovarian and uterine  stem cells and Spermatogonial stem cells in the treatment of infertility caused by chemotherapy, autoimmune diseases, diseases associated with X chromosome, environmental hazards, adolescence endometriosis or ovarian cysts and ovarian cancer before menopause, fertility preservation, prevention of transmission of genetic diseases are from the application of stem cells in medical sciences that some of them has been reviewed and approved in animals and humans, and some only in animals. Conclusion: Stem cells can be used in the treatment of reproductive disorders in women and men; however there are technical and ethical challenges in the use of stem cells in human samples which need more contemplation.